2021
DOI: 10.1016/j.jstrokecerebrovasdis.2020.105479
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Informing Community Emergency Cardiovascular Disease Preparedness during the COVID-19 Pandemic: Stroke Ready

Abstract: Introduction: Acute stroke and acute myocardial infarction (AMI) treatments are time sensitive. Early data revealed a decrease in presentation and an increase in pre-hospital delay for acute stroke and AMI during the coronavirus disease 2019 (COVID-19) pandemic. Thus, we set out to understand community members' perception of seeking acute stroke and AMI care during the COVID-19 pandemic to inform strategies to increase cardiovascular disease preparedness during the pandemic. Methods: Given the urgency of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Similar to our study, a survey of stroke centres in China showed a 45% reduction in TIA and 32% in stroke admissions in mild epidemic regions, as well as overall increased delays to acute stroke care [ 33 ]. Although the reasons for increased onset-to-door delays are unclear, fear of virus exposure in the ambulance or at the hospital and absence of bystanders to initiate the stroke alarm during social distancing mandate might have delayed initiation of the EMS call [ 34 ]. Also, the need to perform additional respiratory screening and use of personal protective equipment could increase prehospital delays.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, a survey of stroke centres in China showed a 45% reduction in TIA and 32% in stroke admissions in mild epidemic regions, as well as overall increased delays to acute stroke care [ 33 ]. Although the reasons for increased onset-to-door delays are unclear, fear of virus exposure in the ambulance or at the hospital and absence of bystanders to initiate the stroke alarm during social distancing mandate might have delayed initiation of the EMS call [ 34 ]. Also, the need to perform additional respiratory screening and use of personal protective equipment could increase prehospital delays.…”
Section: Discussionmentioning
confidence: 99%
“…The T 89 until 1990, from 2008 to 2018, and the years 2020 and 2021; the T 28 from 1990 to 2007; the T 46 in 2019; and the T 64 in 2022. Between domains T 93 and T 89 , the most relevant works are: a paper on community preparedness for cardiovascular emergencies during the COVID-19 pandemic [68]; and a comparison of arrhythmia diagnosis in human-dependent versus algorithm-dependent systems [69]. At the date of these articles (2021), as we mentioned previously, the labels of the T 89 topic are "assay" and "detection".…”
Section: Cross-domain Document Validationmentioning
confidence: 99%
“…corona in the ambulance and in the hospital. Community members' attitudes and perceived behavioral control to seek emergency cardiovascular care are affected by the COVID-19 pandemic (Robles et al, 2021).…”
Section: Original Articlementioning
confidence: 99%